APLIKASI REGRESI DATA PANEL UNTUK PEMODELAN TINGKAT PENGANGGURAN TERBUKA KABUPATEN/KOTA DI PROVINSI JAWA TENGAH - Tyas Ayu Prasanti; Triastuti Wuryandari; Agus Rusgiyono (Jurnal Gaussian, 2015)
Open unemployment rate is the percentage of the labor force that is unemployed and actively seeking employment to the total labor force. Unemployment data is a combination of cross section data and time series data are commonly called panel data. This study aims to be modeling the open unemployment rate in Central Java province in 2008 to 2013 by using panel data regression. To estimate the panel data regression model, there are three approaches, the common effect model, fixed effect model and random effects model. Estimation of panel data regression model is used the fixed effect model with cross section weight. The model show that the percentage of population aged 15 years and over who worked by the highest education attained is Senior High School/Vocational School, Senior High School Gross Enrollment Rate (GER), dependency ratio and Gross Regional Domestic Product (GDP) significantly affect the open unemployment rate by generating  for 81,65 %. Keywords: Cross Section Weight, Fixed Effect Model, Panel Data Regression, Open Unemployment, Central Java Province